Camera as weapon: ways of seeing in Kashmir. Issue 3 (2nd September 2019) - Nath, Anjali
ABSTRACT: This article considers amateur images that came out of Indian occupied Kashmir during the summer of 2016. These pictures, circulated on Facebook and Twitter, documented the human cost of India's use of pellet guns for anti-protest crowd dispersal, a decision that led to the gruesome blindings and wounding of Kashmiris. Pictures of pellet gun victims sparked outrage online as they spread across a social media already saturated with several competing visions of Kashmir's past, present, and future. Countless images of maimed Kashmiris entered a visual field structured by the Indian state's pervasive surveillance of Kashmiri aspirations for azaadi . Writing in the wake of Third Cinema's vision of the camera as a weapon, this piece considers the relationship between the insurgent's right to look and right to maim summoned by the liberal state. Reflecting on the significance of particular networks of circulation, registers of representation, and forms of enunciation, I offer a rethinking of documentation, documentary images, and ways of seeing in Kashmir.